Observational Study to Compare Transdermal Nitroglycerin and Placebo Patch in Enhancing the Post-Operative analgesic Effect of Intrathecal Clonidine with Bupivacaine in Abdominal Hysterectomies - Pooja Shah; Kandarp Vyas; Dinesh K. Chauhan; Jigisha Mehta (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Hyperbaric Bupivacaine 0.5% is the most commonly used for spinal anaesthesia.To improve thequality & duration of analgesia many adjuvants have been used.Intrathecal clonidine binds with postsynapticalpha-2 receptors at the dorsal horn of the spinal cord,resulting in anti-nociceptive action.Transdermalnitroglycerin (tNTG) has been found to be converting nitroglycerin to Nitric Oxide(NO),which results inpain modulation in the central and peripheral nervous system by cyclic Guanosine Monophosphate(cGMP)through which the post-operative analgesia effect enhances.Method: Sixty patients Of ASA I/II aged between 20to60 years posted for hysterectomy under spinalanaesthesia were selected.Patients were randomly allotted into 2 equal groups.Group A received:Hyperbaric bupivacaine 0.5% (17.5 mg)+clonidine(50 mcg) + placebo patchGroup B received:hyperbaric bupivacaine0.5% (17.5 mg) + clonidine (50 mcg) + nitroglycerin (tntg)patch(nitroglycerin 25 mg/patch)We have observed onset and duration of sensory.and motor block,two segment regression time, duration ofanalgesia, hemodynamic changes and complication if any.Results: There was no statistically significant difference in demographic data and onset and duration ofmotor and sensory block. Duration of analgesia was significantly prolonged in clonidine with tNTG groupas compared to clonidine group with placebo group.Conclusion: Transdermal Nitroglycerin patch with intrathecal clonidine prolonged duration of analgesiawithout any changes in onset and duration of sensory and motor block.